Surgical optimization of motor recovery in face transplantation - Aycart, Mario A.; Perry, Bridget; Alhefzi, Muayyad; Bueno, Ericka M.; Kueckelhaus, Maximilian; Fischer, Sebastian; Pomahac, Bohdan (The journal of craniofacial surgery, 2016)
Background: - Face transplantation (FT) has emerged as a viable option for treating devastating facial injuries. Most reported outcomes have demonstrated satisfactory motor and sensory restoration despite differences in technique. The authors have developed an algorithm of facial nerve management in these challenging patients. Our principles of management are illustrated by 2 specific patients. - Methods: - A retrospective analysis of prospectively collected data on 2 full face transplants was performed. Both patients required nerve grafting during full FT. Patient 1 due to short donor facial nerve stumps and patient 2 due to intraoperative soft tissue swelling. Patient 2 required a nerve transfer 11 months after full FT due to impaired motor recovery opposite the side of nerve grafting. Follow-up examinations consisting of manual muscle testing and Sunnybrook Facial Grading System 6 to 42 months after full FT with selected video examinations were critically reviewed. - Results: - Patient 1 had symmetrical motor recovery with gradual improvements noted throughout. At 6 months, Patient 2 had asymmetrically improving motor function. After nerve transfer, the patient showed gradual improvement in motor recovery, symmetry, and tone. Videos for each patient demonstrate the evolution of the patients’ ability to smile from 6 to 42 months. - Discussion: - The authors describe their assessment of motor recovery and management of facial nerve reconstruction as it pertains to FT. Finally, the authors illustrate the principles of nerve transfer are applicable to FT recipients.
Gesehen am 19.08.2020